PENGARUH SHARED REALITY TERHADAP KEBAHAGIAAN PADA PENGGUNA MEDIA SOSIAL USIA DEWASA MENENGAH - Aulia Rahmita; Lita Ariani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Social media has been used by various age groups, including middle-aged adults. Thepurpose of this study was to determine the effect of shared reality on happiness in middle-aged adult social media users. The hypothesis of this study is that there is an effect ofshared reality on happiness in middle-aged adult social media users. The subjects of thisstudy were 111 people, with the criteria of individuals aged 40-60 years, having socialmedia, and actively using social media to share their daily activities and communicate.Measurements were made using a shared reality scale and a happiness scale. The dataanalysis method used is a simple linear regression test using SPSS 23.0 (StatisticalPackages for the Social Sciences The results of this study indicate that there is an effect,with a regression value of t = 4.004 and a significance of 0.000 (<0.05). These resultsindicate that there is a significant influence between shared reality on happiness in middle-aged adult social media users.